2021
DOI: 10.1007/s00394-021-02502-6
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational supplementation with eicosapentaenoic acid reduced the metabolic consequences on the whole body and skeletal muscle in mice receiving an obesogenic diet

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Protection of offspring from weight gain, oxidative stress, and alteration in FA oxidation was demonstrated in animals with Fat1 overexpression that could increase the bioconversion of n-6 to n-3 PUFA [29]. We previously reported that transgenerational intake of EPA (provided by fish oil rich in EPA) could reduce body fat gain and cardiometabolic risk in offspring from the third generation when fed an obesogenic diet [23]. The current study aimed to investigate the specific transcriptomic adaptations in VAT during the development of obesity in these mice, which were compared to a control lineage that received an isocaloric supplementation with a high-oleic sunflower oil.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Protection of offspring from weight gain, oxidative stress, and alteration in FA oxidation was demonstrated in animals with Fat1 overexpression that could increase the bioconversion of n-6 to n-3 PUFA [29]. We previously reported that transgenerational intake of EPA (provided by fish oil rich in EPA) could reduce body fat gain and cardiometabolic risk in offspring from the third generation when fed an obesogenic diet [23]. The current study aimed to investigate the specific transcriptomic adaptations in VAT during the development of obesity in these mice, which were compared to a control lineage that received an isocaloric supplementation with a high-oleic sunflower oil.…”
Section: Discussionmentioning
confidence: 99%
“…The current study aimed to investigate the specific transcriptomic adaptations in VAT during the development of obesity in these mice, which were compared to a control lineage that received an isocaloric supplementation with a high-oleic sunflower oil. We have previously reported the limitation of fibrotic, inflammatory, and anti-metabolic processes in the muscle and liver from these animals [23,24]. However, the biological and molecular adaptations induced by transgenerational intake of n-3 PUFA in the AT remained to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations